Metode “King of Brama” sebagai pengembangan inovasi masa endemi Komunitas Sambel Pecel klegen Kota Madiun - Kharisma, Anggi Cahya; Nurhayati, Puji (Nur Science Institute, 2021)
People's lives today cannot be separated from the existence of Micro Small and Medium Enterprises (MSMEs). The role of MSMEs is considered significant to the improvement of the Indonesian economy and is also able to absorb labor on a considerable scale. The problems faced by MSMEs today are marketing, branding and packaging. Likewise, with the problems faced by the Sambel Pecel community of Klegen village of Madiun city. Digital marketing is very important and crucial that must be done in order to compete in the global market. The purpose of this training is to provide innovation in product packaging or build a more modern brand to the MSMEs community Sambel Pecel Kota Madiun, as an increase in sales turnover during the covid-19 pandemic. The implementation method is carried out using several stages, namely 1) identifying the problem, 2) identifying the output, and 3) conducting training. The result of this activity is the innovation of Sambel Pecel products that have more modern packaging and branding. This activity is expected to make the Sambel Pecel MSME community develop and improve its marketing methods by using digital marketing.